2015
DOI: 10.1007/s00134-015-3646-z
|View full text |Cite
|
Sign up to set email alerts
|

Preemptive enteral nutrition enriched with eicosapentaenoic acid, gamma-linolenic acid and antioxidants in severe multiple trauma: a prospective, randomized, double-blind study

Abstract: This study failed to show a significant benefit for the preemptive use of the study formula in patients with severe trauma. Additional studies need to be performed in which the amount of supplementation is targeted to a potentially measurable endpoint, e.g. the O-3I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 36 publications
2
27
4
1
Order By: Relevance
“…Glenn and Wischmeyer [245] analyzed separately the studies administering omega-3 FA as a bolus or in a continuous manner and found that continuous administration improved length of stay and length of ventilation; in contrast, bolus administration had no advantage. The pre-emptive administration of the same formula administered in the first 3 studies in severe, ventilated, multiple trauma patients did not find any advantage [239]. In this study, the membrane content of EPA and DHA was very low at baseline and was hardly corrected with omega-3 and borage oil administration, suggesting that we do not know the exact amount of omega-3 FA to administer to this category of patients.…”
Section: Commentary To Recommendations 30 -32contrasting
confidence: 58%
See 1 more Smart Citation
“…Glenn and Wischmeyer [245] analyzed separately the studies administering omega-3 FA as a bolus or in a continuous manner and found that continuous administration improved length of stay and length of ventilation; in contrast, bolus administration had no advantage. The pre-emptive administration of the same formula administered in the first 3 studies in severe, ventilated, multiple trauma patients did not find any advantage [239]. In this study, the membrane content of EPA and DHA was very low at baseline and was hardly corrected with omega-3 and borage oil administration, suggesting that we do not know the exact amount of omega-3 FA to administer to this category of patients.…”
Section: Commentary To Recommendations 30 -32contrasting
confidence: 58%
“…However, even higher doses were not associated with complications. Enteral formulae enriched in borage oil and/or omega-3 FA have been administered in patients suffering from ARDS, acute lung injury (ALI) and sepsis with positive effects regarding length of stay, length of ventilation and even mortality [233,234,239,242]. These four studies used the same study and control formulae.…”
Section: Commentary To Recommendations 30 -32mentioning
confidence: 99%
“…Those with low levels at day 6 had significantly more infection, longer ICU, and hospital stay. The same trend was found by Kagan et al [11] after preemptively administrating enteral feeding enriched in omega-3 fatty acids and gamma-linolenic acid in trauma patients. Again no difference was found between the study and the control group but levels of membrane omega-3 index failed to reach therapeutic levels even after 7 days of therapy.…”
Section: Introductionsupporting
confidence: 84%
“…Ìè âèä³ëèëè â³ñ³ì äîñë³äaeåíü [233][234][235][236][237][238][239][240], ïðèñâÿ÷åíèõ öüîìó ïèòàííþ; â ÷îòèðüîõ ç íèõ òàêîae çàñòîñîâóâàëèñü àíòèîêñèäàíòè. Ìåòà-àíàë³ç íå âèÿâèâ aeîäíèõ ïåðåâàã (äèâ.…”
Section: êîìåíòàð äî ðåêîìåíäàö³é 30-32unclassified